POST-EXTRACTION HEMORRHAGE: ASSESSING HYPERTENSION AS A RISK FACTOR IN DENTAL EXTRACTIONS - Amelia Elizabeth Pranoto; Nina Runting; Eddy Hermanto (Indonesian Journal of Dentistry, 2025)
Background: Tooth extraction, a frequently performed dental procedure, typically culminates in hemostasis within several hours post-operatively. Hypertensive individuals exhibit a propensity for protracted bleeding following surgical interventions. This investigation seeks to assess prolonged bleeding after dental extraction in hypertensive patients. The study aims to determine whether elevated blood pressure is the sole etiological factor in prolonged bleeding or if other confounding variables are implicated. Methods: This prospective cohort study was conducted at Wates Public Hospital, Yogyakarta, Indonesia, from October 2024 to February 2025. Consecutive sampling was used in this study. All research subjects were patients at the Oral and Maxillofacial Surgery Clinic of the RSUD Wates who underwent closed-method extraction using local anesthesia. Patients were separated into two groups, normal and hypertension. Seventy-four patients have been involved in this research, based on inclusive and exclusive criteria. Confounding factors which could influenced blood pressure were controlled statistically.Outcome: Findings indicate that increased mean arterial pressure may extend bleeding time after extraction (p < .001). Conclusion: Elevated mean arterial pressure may prolong bleeding following tooth extraction. Furthermore, several confounding factors, including patients’ pharmacotherapy, localized inflammation resulting from periodontal disease in hypertensive individuals, and adverse patient behaviors after extraction, should be taken into consideration.